Conflict Marriage Between Sayyid and Non Sayyid in Takalar Regency - Arwani, Nurindah; Bahfiarti, Tuti; Farid, Muhammad (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The purpose of this research is to gain further insight into the marriage experiences of Sayyid women in Cikoang Village, Takalar Regency, South Sulawesi. Using qualitative research methods such as observation, interviews, and documentation, the research project investigates the backgrounds of Sayyid women who marry non-Sayyid men and assesses the consequent effect on familial connections within the system of marriage of other descendants in Cikoang Village, Takalar Regency. The main objectives of this study are twofold: first, to explain the history of Sayyid women, and second, to examine the effects of family disputes on the system of marriage among Sayyid descendants in Cikoang Village, Takalar Regency. The Sayyid community's complex concerns, which cause family conflicts, vary and are intertwined with both internal familial regulations and larger cultural standards. Typically, disputes within the Sayyid community arise when women choose to marry outside their clan, pick partners who are not of Sayyid heritage, and eventually decide to leave or disassociate themselves from their family.